2020
DOI: 10.1039/d0bm01209b
|View full text |Cite
|
Sign up to set email alerts
|

The progress in corneal translational medicine

Abstract: Cornea tissue is in high demand by tissue donation centres globally, and thus tissue engineering cornea, which is the main topic of corneal translational medicine, can serve as a limitless alternative to a donated human cornea tissue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 265 publications
(287 reference statements)
0
17
0
Order By: Relevance
“…Some of these kinds of biodegradable polymers have shown that threedimensional scaffolds can allow the diffusion of nutrients and also support cell adhesion, proliferation and differentiation for functional tissue regeneration [12][13][14]. More precisely, a good amount of research has been conducted by different researchers globally using various polymeric and synthetic biomaterials for many applications within the human body which mainly have used electrospinning technique including in the breast [15], bone [16,17], nerves [18], dental [19,20], skin [21][22][23], cornea and contact lenses [24][25][26][27][28][29][30], blood vessels [31], ligaments [32], diaphragm [33], trachea [34,35], lung [36], cartilage [37], bladder [38] and intestine [39], and all of the mentioned tissues have involved the same principle.…”
Section: Introductionmentioning
confidence: 99%
“…Some of these kinds of biodegradable polymers have shown that threedimensional scaffolds can allow the diffusion of nutrients and also support cell adhesion, proliferation and differentiation for functional tissue regeneration [12][13][14]. More precisely, a good amount of research has been conducted by different researchers globally using various polymeric and synthetic biomaterials for many applications within the human body which mainly have used electrospinning technique including in the breast [15], bone [16,17], nerves [18], dental [19,20], skin [21][22][23], cornea and contact lenses [24][25][26][27][28][29][30], blood vessels [31], ligaments [32], diaphragm [33], trachea [34,35], lung [36], cartilage [37], bladder [38] and intestine [39], and all of the mentioned tissues have involved the same principle.…”
Section: Introductionmentioning
confidence: 99%
“…[ 171 ] Clinical assessment of novel bioengineered stromal constructs is limited. [ 172 ] Animal trials performed have been discussed throughout this text, with varying degrees of success. The latest stromal constructs on the market, such as the CorNeat KPro, focus on 100% synthetic, nonbiodegradable materials in a similar way to the established Boston KPro.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike other engineered tissues, the artificial cornea must have excellent optical transparency to admit light [120] , [121] , [122] , [123] . The human amniotic membrane is most widely used because it contains growth factors with low immunogenicity [124] , [125] , [126] , but its transparency is poor due to its thick seroma layer (shown in Fig. 6 b).…”
Section: Tissue Engineeringmentioning
confidence: 99%